Managerial Objectives: A Retrospective on Utility Maximization in Pro Team Sports. (February 2015) - Fort, Rodney
Abstract This is an essay review of the literature on utility maximization as a managerial objective in pro team sports. It ends up that there is a heretofore‐unrecognized parallel development of the idea, in English football by Sloane [Scottish Journal of Political Economy (1971), 17, 121] and in North American pro sports by Quirk and El Hodiri, presented in that same year but not published as a conference proceeding until 1974. I review these works and place the rest of the extant literature chronologically, noting their level of generality along a couple of dimensions. I also observe a lack of a clear reference lineage in this literature and suggest one. Adopting it should aid future researchers who are trying to place their work in the context of this literature. [It would have helped me, for example.]